2016
DOI: 10.1371/journal.pone.0168599
|View full text |Cite
|
Sign up to set email alerts
|

Temperature Sensitivity of Soil Respiration to Nitrogen Fertilization: Varying Effects between Growing and Non-Growing Seasons

Abstract: Nitrogen (N) fertilization has a considerable effect on food production and carbon cycling in agro-ecosystems. However, the impacts of N fertilization rates on the temperature sensitivity of soil respiration (Q10) were controversial. Five N rates (N0, N45, N90, N135, and N180) were applied to a continuous winter wheat (Triticum aestivum L.) crop on the semi-arid Loess Plateau, and the in situ soil respiration was monitored during five consecutive years from 2008 to 2013. During the growing season, the mean soi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0
6

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 32 publications
(36 reference statements)
2
9
0
6
Order By: Relevance
“…Our results, together with those of previous studies (Hawkins et al, 2007;Wang et al, 2009;Zhou et al, 2016), showed that the values of E for both the α and β diversities of the most diverse microbes may be lower than the predicted range of 0.60-0.70 eV (Brown et al, 2004;Allen et al, 2005). For reference, the E-values were expressed in terms of Q 10 , which is defined as the rate of change with a 10°C increase in temperature and were calculated according to Liu et al (2016). The E-values for bacteria (0.047 eV) and the functional genes (0.341 eV) are equivalent to Q 10 values of 1.07 and 1.64; therefore, the spatial turnover of the soil microbial community increases c. 1.1-1.6 times for every 10°C increase in mean annual environmental temperature.…”
Section: Discussionsupporting
confidence: 50%
See 1 more Smart Citation
“…Our results, together with those of previous studies (Hawkins et al, 2007;Wang et al, 2009;Zhou et al, 2016), showed that the values of E for both the α and β diversities of the most diverse microbes may be lower than the predicted range of 0.60-0.70 eV (Brown et al, 2004;Allen et al, 2005). For reference, the E-values were expressed in terms of Q 10 , which is defined as the rate of change with a 10°C increase in temperature and were calculated according to Liu et al (2016). The E-values for bacteria (0.047 eV) and the functional genes (0.341 eV) are equivalent to Q 10 values of 1.07 and 1.64; therefore, the spatial turnover of the soil microbial community increases c. 1.1-1.6 times for every 10°C increase in mean annual environmental temperature.…”
Section: Discussionsupporting
confidence: 50%
“…For reference, the E ‐values were expressed in terms of Q 10 , which is defined as the rate of change with a 10°C increase in temperature and were calculated according to Liu et al . (2016). The E ‐values for bacteria (0.047 eV) and the functional genes (0.341 eV) are equivalent to Q 10 values of 1.07 and 1.64; therefore, the spatial turnover of the soil microbial community increases c .…”
Section: Discussionmentioning
confidence: 99%
“…? /NO 2 -/NO 3 -) limitation (Liu et al 2016;Wang et al 2010), although in this study only total peat nitrogen was assessed and this did not differ significantly between peat types. The lack of significant difference in temperature sensitivity of CO 2 and CH 4 production with glucose addition may be because despite an increase in carbon lability, unamended peats still had sufficient available carbon for respiration due to high organic matter content (Dai et al 2017).…”
Section: Discussionmentioning
confidence: 87%
“…Most studies that have investigated soil C dynamics were performed in ecosystems where human disturbance is relatively rare, such as forest ecosystems (Casals R S rates in wheat (Liu et al, 2016). For HW and PW, no R S peaks were detected immediately after application of N fertilizer.…”
Section: Soil Respiration and Management Practicesmentioning
confidence: 99%